IMPACT OF TRADE FINANCE ON AGRICULTURAL EXPORT GROWTH IN NIGERIA - Adeyemi, John Olanrewaju; Mojekwu, Ogechukwu Rita (Scholars Digest Publishing, 2026)
This study investigates the effect of trade finance on the growth of agricultural exports in Nigeria over the period 1990–2024. Employing the Autoregressive Distributed Lag (ARDL) framework, the research explores both the short-run and long-run interactions between agricultural exports and trade finance. Agricultural export performance is represented by raw material exports as a percentage of total merchandise exports, while trade finance is proxied by domestic credit to the private sector as a percentage of GDP. The model also incorporates GDP growth, exchange rate, and inflation as control variables. Empirical findings reveal a statistically significant and positive long-run association, indicating that a 1% increase in trade finance corresponds to a 0.45% rise in agricultural exports. The error correction mechanism further demonstrates a moderate adjustment speed, with approximately 32% of short-run disequilibrium corrected annually. Additionally, GDP growth and exchange rate exert positive influences on agricultural exports, whereas inflation has an adverse effect. The study recommends strengthening financial institutions to improve trade finance access, fostering public–private partnerships to reduce risks in agricultural lending, and implementing targeted credit initiatives for SMEs. These policy measures are expected to ease financing constraints and enhance the performance of Nigeria’s agricultural export sector, thereby supporting economic diversification and sustainable growth.
Keywords: Trade Finance, Agricultural Export, Agricultural Export Growth, Nigeria.